Implementation of Collaborative Counseling Services to Improve Reproductive Health Muslim Marriage Candidates - Naser, Muhammad Nikman; Hayati, Inaya (UIN Fatmawati Sukarno Bengkulu, 2022)
The problem faced today is that reproductive health for prospective or married couples tends to be ignored. In addition, the provision of intensive counseling services is limited considering that reproductive health problems can disrupt the biological and psychological conditions of individuals. The purpose of this study is to provide an overview and framework of collaborative counseling services that can be adopted for KUA (Religion Office) extension workers, family counselors and consultants. The method used is a qualitative descriptive approach. The results showed that collaborative counseling services can be an alternative solution in improving reproductive health and psychologically strengthening Muslim brides-to-be. Counselors, religious instructors, health institutions can work together in the implementation of collaborative counseling services.